Acute liver failure caused by paracetamol intoxication in a severely depressed patient with suicidal intent: A case report - Pratama, Erdilian; Rosandy, Milanitalia (Deka in Medicine, 2024)
BACKGROUND: Paracetamol poisoning has extensive implications, and one of the most dangerous is the involvement of liver dysfunction. Such cases are rare but require comprehensive evaluation and management. CASE: A 19-year-old female presented to the Emergency Department (ED) with nausea, vomiting, and epigastric pain after ingesting 20 grams of paracetamol with alcohol in a suicide attempt. Her history revealed severe depression with symptoms of anhedonia, anergy, and self-harming behavior. Laboratory results showed elevated liver enzymes and prolonged coagulation time, though other organ functions were normal. She was diagnosed with acute liver failure due to paracetamol intoxication and was treated with N-acetylcysteine (NAC), omeprazole, ondansetron, vitamin K, and psychiatric counseling. After seven days of hospitalization, her clinical condition improved, with plans for outpatient follow-up and prescribed medications. CONCLUSION: This case highlights the importance of addressing adolescent mental health and providing education on the dangers of drug overdose, along with access to psychological support to prevent self-harm.